Penerapan Fintech Dalam Strategi Bisnis Internasional - Sahata Sitanggang, Andri; Azhar Aulia, Akhmad; Quikly Wahyudi, Viki; Gradiansya, Aqbil; Asfy Putri, Nadhilla (Master Manajemen, 2024)
Financial technology (fintech) has become a major driver of transformation in the global banking sector, offering innovative solutions that not only enhance operational efficiency but also expand the reach and quality of financial services. This study aims to explore how international banks integrate fintech technologies into their business strategies to remain competitive in the ever-evolving global market. By analyzing data from various sources, including case studies of leading banks and academic literature, this study highlights the strategic and operational impacts of fintech adoption. The findings indicate that the implementation of fintech not only improves transaction efficiency and security but also opens new market opportunities and promotes global financial inclusion. However, this study also identifies several challenges in fintech implementation, such as complex regulations and cybersecurity threats, and provides recommendations for effective implementation strategies to overcome these barriers.